PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL BERBASIS VIDEO ANIMASI EDUKATIF MENGGUNAKAN INSHOT APPLICATION PADA MATA PELAJARAN IPAS DI KELAS III SEKOLAH DASAR - Ayu Septiah Utami; Hendra Budiono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop and evaluate the validity and practicality of a digital learning media based on educational animated videos for Grade III elementary school IPAS lessons on the topic “The City/Regency Where I Live.” The research employed a Research and Development (R&D) method using the ADDIE model. The media was developed using the InShot application and produced a video consisting of an introduction, material presentation, interactive quizzes, and a closing section. Validation results indicated a very valid category, with scores of 4.6 from the material expert, 4.7 from the design expert, and 4.7 from the language expert. Practicality assessments by teachers (4.7), small-group trials (4.5), and large-group trials (4.7) showed that the media was highly practical. Thus, the developed animated video-based digital learning media is considered feasible and practical for use in the learning process.